The Influence of Ownership Structure on Financial Distress - Annisa, Annisa; Luky, Lila Ariana; Martian, Vanesa; Astuti, Christina Dwi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Fluctuating economic conditions in the post-pandemic era have increased the risk of financial failure across various industrial sectors in Indonesia. This phenomenon necessitates more stringent oversight mechanisms through corporate governance to ensure business continuity. This research aims to analyze and obtain empirical evidence regarding the influence of ownership structure projected through managerial ownership, institutional ownership, and public ownership on financial distress in companies included in the special notation 'E' on the Indonesia Stock Exchange (IDX). Purposive sampling is used in this study's quantitative methodology. Annual reports covering the years 2019–2023 provided secondary data. Because the dependent variable is dichotomous (categorical), logistic regression is the data analysis method employed. The study's conclusions show that managerial ownership significantly lowers financial distress, indicating that successfully balancing managers' and shareholders' interests lowers the likelihood of failure. Enhancing external monitoring was also found to be significantly influenced by institutional ownership. Financial suffering is unaffected by public ownership. As a monitoring tool for reducing financial risks, ownership structure is essential. Companies with an appropriate concentration of ownership tend to be more resilient to financial pressure. This study provides updated data for the post-pandemic period and integrates various agency theories within the context of the Indonesian capital market.